Answer:
He saw <u>1 duck</u> and <u>3 dogs</u>.
Step-by-step explanation:
Given:
Evan went to the park and saw four animals.
Each animal was either a duck or a dog.
He saw a total of 14 legs.
Now, to find the number of each animal he had seen.
Let the number of duck be ![x.](https://tex.z-dn.net/?f=x.)
And the number of dog be ![y.](https://tex.z-dn.net/?f=y.)
So, total number of animals:
![x+y=4\\y=4-x](https://tex.z-dn.net/?f=x%2By%3D4%5C%5Cy%3D4-x)
Now, the total number of legs he did see:
<em>As we know the legs of a duck are 2 and a dog are 4.</em>
Adding both sides by -16 we get:
![-2x=-2](https://tex.z-dn.net/?f=-2x%3D-2)
Dividing both sides by -2 we get:
![x=1](https://tex.z-dn.net/?f=x%3D1)
The number of duck = 1.
Now, putting the value of
in above equation we get:
![y=4-x](https://tex.z-dn.net/?f=y%3D4-x)
![y=4-1\\y=3.](https://tex.z-dn.net/?f=y%3D4-1%5C%5Cy%3D3.)
The number of dogs = 3.
Therefore, he saw 1 duck and 3 dogs.
Answer:
![(x-9)^2-87](https://tex.z-dn.net/?f=%28x-9%29%5E2-87)
Step-by-step explanation:
Answer:
61,239,550
Step-by-step explanation:
We let the random variable X denote the IQ scores. This would imply that X is normal with a mean of 100 and standard deviation of 17. We proceed to determine the probability that an individual chosen at random from the population would be a genius, that is;
Pr( X>140)
The next step is to evaluate the z-score associated with the IQ score of 140 by standardizing the random variable X;
![Pr(X>140)=Pr(Z>\frac{140-100}{17})=Pr(Z>2.3529)](https://tex.z-dn.net/?f=Pr%28X%3E140%29%3DPr%28Z%3E%5Cfrac%7B140-100%7D%7B17%7D%29%3DPr%28Z%3E2.3529%29)
The area to the right of 2.3529 will be the required probability. This area from the standard normal tables is 0.009314
From a population of 6,575,000,000 the number of geniuses would be;
6,575,000,000*0.009314 = 61,239,550
June is correct because <span>12 is a </span>multiple<span> of both </span>3 and 4<span>.</span>
Question is Incomplete, Complete question is given below.
Prove that a triangle with the sides (a − 1) cm, 2√a cm and (a + 1) cm is a right angled triangle.
Answer:
∆ABC is right angled triangle with right angle at B.
Step-by-step explanation:
Given : Triangle having sides (a - 1) cm, 2√a and (a + 1) cm.
We need to prove that triangle is the right angled triangle.
Let the triangle be denoted by Δ ABC with side as;
AB = (a - 1) cm
BC = (2√ a) cm
CA = (a + 1) cm
Hence,
Now We know that
![(a- b)^2 = a^2+b^2 - 2ab](https://tex.z-dn.net/?f=%28a-%20b%29%5E2%20%3D%20a%5E2%2Bb%5E2%20-%202ab)
So;
![{AB}^2= a^2 + 1^2 -2\times a \times1](https://tex.z-dn.net/?f=%7BAB%7D%5E2%3D%20a%5E2%20%2B%201%5E2%20-2%5Ctimes%20a%20%5Ctimes1)
![{AB}^2 = a^2 + 1 -2a](https://tex.z-dn.net/?f=%7BAB%7D%5E2%20%3D%20a%5E2%20%2B%201%20-2a)
Now;
![{BC}^2 = (2\sqrt{a})^2= 4a](https://tex.z-dn.net/?f=%7BBC%7D%5E2%20%3D%20%282%5Csqrt%7Ba%7D%29%5E2%3D%204a)
Also;
![{CA}^2 = (a + 1)^2](https://tex.z-dn.net/?f=%7BCA%7D%5E2%20%3D%20%28a%20%2B%201%29%5E2)
Now We know that
![(a+ b)^2 = a^2+b^2 + 2ab](https://tex.z-dn.net/?f=%28a%2B%20b%29%5E2%20%3D%20a%5E2%2Bb%5E2%20%2B%202ab)
![{CA}^2= a^2 + 1^2 +2\times a \times1](https://tex.z-dn.net/?f=%7BCA%7D%5E2%3D%20a%5E2%20%2B%201%5E2%20%2B2%5Ctimes%20a%20%5Ctimes1)
![{CA}^2 = a^2 + 1 +2a](https://tex.z-dn.net/?f=%7BCA%7D%5E2%20%3D%20a%5E2%20%2B%201%20%2B2a)
![{CA}^2 = AB^2 + BC^2](https://tex.z-dn.net/?f=%7BCA%7D%5E2%20%3D%20AB%5E2%20%2B%20BC%5E2)
[By Pythagoras theorem]
![a^2 + 1 +2a = a^2 + 1 - 2a + 4a\\\\a^2 + 1 +2a= a^2 + 1 +2a](https://tex.z-dn.net/?f=a%5E2%20%2B%201%20%2B2a%20%3D%20a%5E2%20%2B%201%20-%202a%20%2B%204a%5C%5C%5C%5Ca%5E2%20%2B%201%20%2B2a%3D%20a%5E2%20%2B%201%20%2B2a)
Hence, ![{CA}^2 = AB^2 + BC^2](https://tex.z-dn.net/?f=%7BCA%7D%5E2%20%3D%20AB%5E2%20%2B%20BC%5E2)
Now In right angled triangle the sum of square of two sides of triangle is equal to square of the third side.
This proves that ∆ABC is right angled triangle with right angle at B.